An alternative synthesis and X-ray crystallographic confirmation of (−)-stepholidine. Issue 19 (11th May 2016) - Gadhiya, Satishkumar V.; Hu, Chunhua; Harding, Wayne W.
Graphical abstract: Highlights: A new synthesis of a key lactone intermediate required for the synthesis of (−)-stepholidine (1 ) was achieved. (−)-Stepholidine was prepared in 23% overall yield in a fourteen-step synthetic sequence. The stereostructure of (−)-stepholidine prepared by this method was confirmed by single crystal X-ray diffraction. Abstract: A formal enantioselective synthesis of (−)-stepholidine that provides an alternative preparation of key lactone intermediate2 is described. The stereostructure of (−)-stepholidine prepared via this method was confirmed by X-ray diffraction.